Con la razón y la fuerza: La Rebelión Popular y la Subjetividad Comunista en los '80 - Bravo, Viviana (Ariadna Ediciones, 2010)
Analysis of the change in the political orientation made in the Communist Party of Chile in the early 80s of last century and the adoption of the policy of Popular Rebellion in their fight against Pinochet